Japan's challenging debt dynamics - Guillemette, Yvan (OECD Publishing, 2014)
A small simulation model is used to evaluate the contribution that the three arrows of the government's strategy - bold monetary policy to achieve higher inflation, flexible fiscal policy and growth-boosting structural reforms - could make to reversing the rise in Japan's public debt ratio, currently about 230% of GDP. The findings indicate that with fiscal consolidation amounting to around 7½ percentage points of GDP by 2020, modestly higher growth coming from increased female labour force participation and higher productivity growth, as well as inflation gradually rising to 2% thanks to unconventional monetary policy measures, the debt ratio could be put on a downward trajectory by the end of this decade, although it is likely to remain above 200% of GDP in 2035. Among the many uncertainties surrounding this scenario, the risk of a larger-than-projected increase in interest rates stands prominently and could prevent the turnaround in debt dynamics. JEL classification codes: E63; H68. Keywords: Japan; debt; deficit; fiscal; budget; projection; simulation; arrow; consolidation; growth; inflation; reform